Contrasting biotic and abiotic drivers of Glomeromycotina and Mucoromycotina mycorrhizal associations in field-grown durum wheat - Elisa Taschen; Esther Guillot; Claude Plassard; Erwan Kerbiriou; Damien Dezette; Adrien Taudière; Aline Personne; Agnès Robin; Dirk Redecker; Philippe Hinsinger (Mycorrhiza, 2026)

Correction to: Tracing Rhizophagus irregularis isolate IR27 in Ziziphus mauritiana roots under field conditions - Babacar Thioye; Dirk Redecker; Diederik van Tuinen; Aboubacry Kane; Sergio Mania de Faria; Dioumacor Fall; Diaminatou Sanogo; Cheikh Ndiaye; Robin Duponnois; Samba Ndao Sylla; Amadou Mustapha Bâ (Mycorrhiza, 2020)

Is a mixture of arbuscular mycorrhizal fungi better for plant growth than single-species inoculants? - Thomas Crossay; Clarisse Majorel; Dirk Redecker; Simon Gensous; Valérie Medevielle; Gilles Durrieu; Yvon Cavaloc; Hamid Amir (Mycorrhiza, 2019)

Four new species of arbuscular mycorrhizal fungi (Glomeromycota) associated with endemic plants from ultramafic soils of New Caledonia - Thomas Crossay; Alexis Cilia; Yvon Cavaloc; Hamid Amir; Dirk Redecker (Mycological Progress, 2018)

A new genus, Planticonsortium (Mucoromycotina), and new combination (P. tenue), for the fine root endophyte, Glomus tenue (basionym Rhizophagus tenuis) - Christopher Walker; Armelle Gollotte; Dirk Redecker (Mycorrhiza, 2018)

A multigene phylogeny demonstrates that Tuber aestivum and Tuber uncinatum are conspecific - Virginie Molinier; Diederik van Tuinen; Gérard Chevalier; Armelle Gollotte; Daniel Wipf; Dirk Redecker (Organisms Diversity & Evolution, 2013)

An evidence-based consensus for the classification of arbuscular mycorrhizal fungi (Glomeromycota) - Dirk Redecker; Arthur Schüßler; Herbert Stockinger; Sidney L. Stürmer; Joseph B. Morton; Christopher Walker (Mycorrhiza, 2013)

Long-term tracing of Rhizophagus irregularis isolate BEG140 inoculated on Phalaris arundinacea in a coal mine spoil bank, using mitochondrial large subunit rDNA markers - Zuzana Sýkorová; Boris Börstler; Soňa Zvolenská; Judith Fehrer; Milan Gryndler; Miroslav Vosátka; Dirk Redecker (Mycorrhiza, 2012)

Importance of dispersal and thermal environment for mycorrhizal communities: lessons from Yellowstone National Park - Ylva Lekberg; James Meadow; Jason R. Rohr; Dirk Redecker; Catherine A. Zabinski (Ecology, 2011)
The relative importance of dispersal and niche restrictions remains a controversial topic in community ecology, especially for microorganisms that are often assumed to be ubiquitous. We investigated the impact of these factors for the community assembly of the root‐symbiont arbuscular mycorrhizal fungi (AMF) by sampling roots from geothermal and nonthermal grasslands in Yellowstone National Park (YNP), followed by sequencing and RFLP of AMF ribosomal DNA. With the exception of an apparent generalist RFLP type closely related to Glomus intraradices , a distance‐based redundancy analysis indicated that the AMF community composition correlated with soil pH or pH‐driven changes in soil chemistry. This was unexpected, given the large differences in soil temperature and plant community composition between the geothermal and nonthermal grasslands. RFLP types were found in either the acidic geothermal grasslands or in the neutral to alkaline grasslands, one of which was geothermal. The direct effect of the soil chemical environment on the distribution of two AMF morphospecies isolated from acidic geothermal grasslands was supported in a controlled greenhouse experiment. Paraglomus occultum and Scutellospora pellucida were more beneficial to plants and formed significantly more spores when grown in acidic than in alkaline soil. Distance among grasslands, used as an estimate of dispersal limitations, was not a significant predictor of AMF community similarity within YNP, and most fungal taxa may be part of a metacommunity. The isolation of several viable AMF taxa from bison feces indicates that wide‐ranging bison could be a vector for at least some RFLP types among grasslands within YNP. In support of classical niche theory and the Baas‐Becking hypothesis, our results suggest that AMF are not limited by dispersal at the scale of YNP, but that the soil environment appears to be the primary factor affecting community composition and distribution.

Unique arbuscular mycorrhizal fungal communities uncovered in date palm plantations and surrounding desert habitats of Southern Arabia - Mohamed N. Al-Yahya’ei; Fritz Oehl; Marta Vallino; Erica Lumini; Dirk Redecker; Andres Wiemken; Paola Bonfante (Mycorrhiza, 2011)

Agroecology: the key role of arbuscular mycorrhizas in ecosystem services - Silvio Gianinazzi; Armelle Gollotte; Marie-Noëlle Binet; Diederik van Tuinen; Dirk Redecker; Daniel Wipf (Mycorrhiza, 2010)

Diversity of mitochondrial large subunit rDNA haplotypes of Glomus intraradices in two agricultural field experiments and two semi‐natural grasslands - BORIS BÖRSTLER; ODILE THIÉRY; ZUZANA SÝKOROVÁ; ALFRED BERNER; DIRK REDECKER (Molecular Ecology, 2010)
Glomus intraradices , an arbuscular mycorrhizal fungus (AMF), is frequently found in a surprisingly wide range of ecosystems all over the world. It is used as model organism for AMF and its genome is being sequenced. Despite the ecological importance of AMF, little has been known about their population structure, because no adequate molecular markers have been available. In the present study we analyse for the first time the intraspecific genetic structure of an AMF directly from colonized roots in the field. A recently developed PCR‐RFLP approach for the mitochondrial rRNA large subunit gene (mtLSU) of these obligate symbionts was used and complemented by sequencing and primers specific for a particularly frequent mtLSU haplotype. We analysed root samples from two agricultural field experiments in Switzerland and two semi‐natural grasslands in France and Switzerland. RFLP type composition of G. intraradices (phylogroup GLOM A‐1) differed strongly between agricultural and semi‐natural sites and the G. intraradices populations of the two agricultural sites were significantly differentiated. RFLP type richness was higher in the agricultural sites compared with the grasslands. Detailed sequence analyses which resolved multiple sequence haplotypes within some RFLP types even revealed that there was no overlap of haplotypes among any of the study sites except between the two grasslands. Our results demonstrate a surprisingly high differentiation among semi‐natural and agricultural field sites for G. intraradices . These findings will have major implications on our views of processes of adaptation and specialization in these plant/fungus associations.

The cultivation bias: different communities of arbuscular mycorrhizal fungi detected in roots from the field, from bait plants transplanted to the field, and from a greenhouse trap experiment - Zuzana Sýkorová; Kurt Ineichen; Andres Wiemken; Dirk Redecker (Mycorrhiza, 2007)

A novel clade of sporocarp-forming species of glomeromycotan fungi in the Diversisporales lineage - Dirk Redecker; Philipp Raab; Fritz Oehl; Francisco J. Camacho; Regis Courtecuisse (Mycological Progress, 2007)

Communities of arbuscular mycorrhizal fungi in arable soils are not necessarily low in diversity - ISABELLE HIJRI; ZUZANA SÝKOROVÁ; FRITZ OEHL; KURT INEICHEN; PAUL MÄDER; ANDRES WIEMKEN; DIRK REDECKER (Molecular Ecology, 2006)
Communities of arbuscular mycorrhizal fungi (AMF) in five agricultural field sites of different management intensities were studied. Variable regions of the ribosomal RNA genes were used to detect and identify AMF directly within colonized roots. Roots from a continuous maize monoculture showed low AMF diversity, in agreement with previous reports on molecular diversity of AMF in agricultural soils. In contrast, a substantially higher diversity of AMF was found throughout the long term ‘DOK’ field experiment, where organic and conventional agricultural practices have been compared side by side since 1978. In this experiment, a 7‐year crop rotation is performed under lower levels of inorganic fertilizer input and chemical pest control. These results are in good agreement with analyses of the spore community previously conducted in these field sites. In a third site, an organically managed leek field with soil of very high phosphate content reflecting the highly intensive conventional field history and intensive tillage, we detected a low‐diversity community comparable to the maize monoculture. In addition to fungi from Glomus group A, which have previously been reported to dominate arable soils, we regularly found members of the genera Scutellospora , Paraglomus and Acaulospora. The genus Acaulospora was shown to occur more frequently early in the growing season, suggesting that the life history strategy of AMF may influence the active community at a given time. These data show that the diversity of AMF is not always low in arable soils. Furthermore, low‐input agriculture involving crop rotation may provide better conditions to preserve AMF diversity, by preventing the selection for the few AMF taxa tolerating high nutrient levels.

Molecular identification and phylogeny of arbuscular mycorrhizal fungi - Dirk Redecker (Plant and Soil, 2002)

Small genets of Lactarius xanthogalactus , Russula cremoricolor and Amanita francheti in late‐stage ectomycorrhizal successions - Dirk Redecker; Timothy M. Szaro; Ryan J. Bowman; Thomas D. Bruns (Molecular Ecology, 2001)
We determined the size of genets of late‐stage ectomycorrhizal fungi in field sites in coastal Northern California. Basidiocarps were collected, mapped and subjected to genetic fingerprinting using amplified fragment length polymorphisms (AFLPs). The minimum size estimates for the largest genets of Amanita francheti , Lactarius xanthogalactus and Russula cremoricolor were 1.5, 9.3 and 1.1 m 2 , respectively. The molecular markers also showed that R. cremoricolor is dimorphic, with red‐ and white‐capped morphotypes of this species forming a continuous population. Our results suggest that spore propagation plays a much more important role in the life history of the Russulaceae in undisturbed forest settings than previously recognized. Fungi appearing late in the succession sequence and systems without obvious disturbance therefore do not necessarily colonize primarily by mycelium.